The Role of Job Satisfaction in Mediating the Effects of the Work Environment, Salary, and Job Promotion on Employee Performance at RSU X - Chornellia Martha Purwaningrum; Imronudin; Siti Soekiswati (Universitas KH. Abdul Chalim Mojokerto, 2026)
Human resources are a key factor in the success of healthcare organizations, particularly hospitals, which are required to provide quality services on an ongoing basis. This study aims to analyze the influence of work environment, salary, and job promotion on employee performance through job satisfaction as an intervening variable at RSU X. This study uses a quantitative approach with a survey method. Data were collected through questionnaires distributed to RSU X employees and analyzed using Structural Equation Modeling with a Partial Least Squares approach (SEM-PLS) through SmartPLS 4.0 software. Model evaluation included testing the validity and reliability of constructs, testing the structural model, and testing direct and indirect hypotheses. The results showed that the work environment, salary, and job promotion had a positive and significant effect on employee job satisfaction. Job satisfaction was also proven to have a positive and significant effect on employee performance. In addition, job satisfaction was able to significantly mediate the effect of the work environment, salary, and job promotion on employee performance. The coefficient of determination (R²) value shows that the research model has strong explanatory power, and the predictive relevance (Q²) value indicates that the model has excellent predictive capability. These findings confirm that improving employee performance in hospitals can be achieved more effectively through efforts to improve the work environment, fair salary management, and a transparent promotion system that takes employee job satisfaction into account.